Focusing properties of radially polarized modified Bessel-modulated Gaussian beam by a high numerical aperture objective. (February 2017) - El Halba, E.M.; Boustimi, M.; Ez-zariy, L.; Belafhal, A.
Abstract: In this paper, the focusing properties of radially polarized modified Bessel-modulated Gaussian (RPMQBG) beam with quadratic radial dependence through a high numerical aperture (NA) lens are investigated, theoretically and numerically, using the vector diffraction theory model. The tight focusing properties are studied in great detail. The numerical simulation results show that the intensity distribution of the RPMQBG beam at the focal region of the numerical aperture can be changed considerably by the variation of the optical vortex beam topological charge l and by the high numerical aperture angle (NA). Highlights: The radially polarized modified Bessel-modulated Gaussian (MQBG) beam is studied. We discuss the focusing characteristics of MQBG beam through a numerical-aperture lens. The total intensity distribution and their components are numerically developed. The effects of the topological charge l and the numerical-aperture angle are shown. A dark regime of the focused polarized MQBG beam is performed with the increase of l .